Role of inflammation in initiation and maintenance of atrial fibrillation in rheumatic mitral stenosis – An analytical cross‐sectional study - Sharma, Gautam (J Arrhythm, 2020)
BACKGROUND: Inflammation has been implicated in the initiation and perpetuation of non‐valvular atrial fibrillation (AF). However, there is a lack of similar data on AF in rheumatic heart disease (RHD). The objective of this study was to analyze the association of inflammation as measured by serum inflammatory biomarkers with AF in rheumatic mitral stenosis (Rh‐MS). METHODS: A comparative cross‐sectional analytical study was conducted on 181 Rh‐MS patients in normal sinus rhythm (NSR; n = 69), subclinical transient AF (SCAF; detected by 24‐hours Holter monitoring; n = 30) and chronic AF (n = 82). Serum hs‐CRP, IL‐6, and sCD‐40L were assessed using ELISA immunoassay and compared in all groups of Rh‐MS with or without AF. RESULTS: We found significantly higher serum hs‐CRP and sCD‐40L levels in the overall AF (Chronic AF + SCAF) group (hs‐CRP: 4.5 ± 3.4 vs 2.3 ± 2.9 mg/L, P < .01; sCD‐40L: 6.4 ± 4.8 vs 3.1 ± 3.4 ng/mL, P < .01) and chronic AF subgroup (hs‐CRP: 4.9 ± 3.4 vs 2.3 ± 2.9 mg/L, P < .01; sCD‐40L: 6.9 ± 5.1 vs 3.1 ± 3.4 ng/mL, P < .01) compared to patients with sinus rhythm. There was a statistically significant graded increase of serum IL‐6 level from the NSR to the SCAF (vs NSR: 6.8 ± 3.9 vs 4.0 ± 2.2 pg/mL, P = .03), and chronic AF subgroups (vs NSR: 9.3 ± 6.5 vs 4.0 ± 2.2 pg/mL, P < .01; vs SCAF: 9.3 ± 6.5 vs 6.8 ± 3.9, P = .05) of atrial fibrillation. CONCLUSIONS: Elevated levels of serum hs‐CRP, IL‐6, and sCD‐40L were strongly associated with overall AF and also with SCAF and chronic AF in Rh‐MS patients indicating a potential role of inflammation in the pathophysiology of rheumatic AF.